Uncle Sam wants you World War I and the making of the modern American citizen - Capozzola, Christopher Joseph Nicodemus, 1971- (Oxford University Press, 2008)
This title tells the dramatic story of the mobilization of the American homefront in World War I. It is an examination of the changing obligations of citizenship and the making of the modern American state in the midst of its participation in the First World War.